2019
DOI: 10.11606/issn.2176-7262.v52i4p311-318
|View full text |Cite
|
Sign up to set email alerts
|

Associação do perfil microbiológico com alterações citológicas em mulheres quilombolas atendidas nas unidades básicas de saúde

Abstract: Objetivo: Analisar o perfil microbiológico e relacionar com as alterações citológicas de mulheres quilombolas que possuem lesões cérvico-vaginais. Material e Métodos. Este foi um estudo de corte transversal de 5 meses, baseado em 154 mulheres quilombolas, na faixa etária de 13 a 74 anos, registradas no Sistema Único de Saúde (SUS) e que possuem lesões cérvico-vaginais. Resultados. Mulheres com idade >45 anos (43,5%) foram as que mais realizaram exames Papanicolaou, seguido das mulheres com 31 a 45 anos (31,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
0
4
0
3
Order By: Relevance
“…In this process, there is greater susceptibility to CC, because these cells are more permissive to HPV infection. 6 Among the 82 patients studied, 34 (41.5%) had cases of vaginal infections, being 21 (25.6%) positive for Gardnerella vaginalis, with a mean age corresponding to 42.4 years, a higher value than that found in Rio Grande do Sul, 9 in women treated at Basic Health Units, with 5.1% cases of Gardnerella vaginalis. A study carried out with quilombola women assisted by the Unified Health System (Sistema Único de Saúde) of municipalities in Maranhão 6 microorganisms is extremely important, as inflammation can camouflage the presence of malignant changes in the smear and facilitate infection by other microorganisms.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…In this process, there is greater susceptibility to CC, because these cells are more permissive to HPV infection. 6 Among the 82 patients studied, 34 (41.5%) had cases of vaginal infections, being 21 (25.6%) positive for Gardnerella vaginalis, with a mean age corresponding to 42.4 years, a higher value than that found in Rio Grande do Sul, 9 in women treated at Basic Health Units, with 5.1% cases of Gardnerella vaginalis. A study carried out with quilombola women assisted by the Unified Health System (Sistema Único de Saúde) of municipalities in Maranhão 6 microorganisms is extremely important, as inflammation can camouflage the presence of malignant changes in the smear and facilitate infection by other microorganisms.…”
Section: Discussionmentioning
confidence: 85%
“…Most of them are not assisted and have limited access to health care, which tends to hamper the gynecological follow-up of women, leaving them more vulnerable to cervicovaginal infections and the development of CC. 6,7 This study aimed to identify factors associated with cervicovaginal infections in quilombola women from Feira de Santana, Bahia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have demonstrated the importance of the Pap smear method for the diagnosis of vaginal infection causing agents (Aragão et al, 2019;Matos-Rocha, 2019;Xavier et al, 2019;Resende et al, 2019). Thus, the objective 3/6 Detection of infections including it's initial stages, and can also identify noncancerous conditions such as infection or inflammation.…”
Section: Agents Causing Genital Infections In Routine Cytological Tests: Frequency and Characteristics Of Papanicolaou Smears 1 Introductmentioning
confidence: 99%
“…O exame citopatológico tem valor como teste de rastreamento e é amplamente difundido no Brasil por estar inserido no Programa Nacional de Prevenção do Câncer do Colo do Útero 16 . Embora o exame citopatológico não seja o teste de escolha para detecção de infecções cervicovaginais, esse método apresentou especificidade entre 93% e 98% para detecção de VB 17 .…”
Section: Introductionunclassified